2014
DOI: 10.1155/2014/282053
|View full text |Cite
|
Sign up to set email alerts
|

Signless Laplacian Spectral Conditions for Hamiltonicity of Graphs

Abstract: We establish some signless Laplacian spectral radius conditions for a graph to be Hamiltonian or traceable or Hamilton-connected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Recently, Chen et al [37], Yu et al [178], and Wei et al [169] independently showed the spectral version of Hamilton-connectedness for graphs with large minimum degree. In 2020, Zhou, Wang and Lu [199] presented the signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree.…”
Section: Problem For K-edge-connectivitymentioning
confidence: 99%
“…Recently, Chen et al [37], Yu et al [178], and Wei et al [169] independently showed the spectral version of Hamilton-connectedness for graphs with large minimum degree. In 2020, Zhou, Wang and Lu [199] presented the signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree.…”
Section: Problem For K-edge-connectivitymentioning
confidence: 99%
“…Fiedler and Nikiforov [9] firstly gave sufficient conditions in terms of the spectral radius of a graph or its complement for the existence of Hamilton cycles. This work motivated further research, one may refer to [1,18,19,23,26,27,28,30]. Recently, by imposing the minimum degree of a graph as a new parameter, Li and Ning [14,15] extended some the results in [9,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Fiedler and Nikiforov [7] gave sufficient conditions on spectral radius for the existence of Hamilton cycles. Motivated by this, there are many other spectral conditions for the Hamiltonicity of graphs, one may refer to [1,14,15,16,19,20,21,22,23]. Recently, by imposing the minimum degree of a graph as a new parameter, Li and Ning [12,13] extended some the results in [7,14,16].…”
Section: Introductionmentioning
confidence: 99%